An Experienced Value of Marital Faithfulness in "Dubin's Lives" - Milhaven, J. Giles (Journal of religious ethics, 1984)
To trace out clearly the moral value of marital faithfulness is an ethical problem of our time. To start a path into the problem, this essay records the experience of one unfaithful spouse and what draws him back to fidelity. The spouse is Bernard Malamud's Dubin, and a reading of Malamud's story is offered in which Dubin returns to his wife because he loves her life. The bulk of the essay aims at drawing clear from the story what this love consists in and how it fittingly moves Dubin to return. Congruent ethical questions are suggested in conclusion.